A Study on the Potential Role of Social Media as a Driving force for Jallikattu Protest - Mary, S Irvin; VV, Deepa Viswam (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Social media platforms like Facebook, Twitter, Whatsapp and Instagram are extensively used to share knowledge around the world, with the power of “Immediate reach” and “Ease to edit”. This ends up in the result of Uncontrollable flow of information reaches to many recipients. This is apparent in the widespread protests in the Middle East and North Africa known as the “Arab Spring” in the years of December 2010-December 2012, and locally in Tamilnadu- India “Pro-Jallikattu Protest” in January 2017. This study tries to find how social media played a vital role to influence the ordinary people as an active participant of Jallikattu protest. How to cite this article: Mary AI, Deepa Viswam V.V. A Study on the Potential Role of Social media as a Driving force for Jallikattu Protest. J Adv Res Jour Mass Comm 2018; 5(4): 41-44. DOI: https://doi.org/10.24321/2395.3810.201817